CHAIRBASED ON TENSEGRITY - P. SHESHIDHAR; SONALI CHOPRA (International Journal of Innovations in Engineering Research and Technology, 2021)
Based on the present modern furniture and the product semantics of the products, there was a rapid change in the present furniture due to the new technologies. The change in the urbanization and the present civilization, the new concept of the Tensegrity came into existence. Tensegrity is a structural design principle that applies to a structure which can be stabilized entirely by internal pre-stress. This pre-stress is created by a discontinuous set of compression elements being opposed and balanced by a continuous tensile force. This combination of balanced parts produces associate exceptionally rigid structure created of members that don't expertise bending moments. The objective of the present paper is to describe the applications of tensegrity structures in Interior Designing.